Understanding the role of social groups in radicalisation - Drake, Deirdre (2014)
The inability to form psychological profiles of individual members across a variety of extremist groups, as well as the recognition in extremism and terrorism research indicates that no adequate personality profile exists. This requires an analysis of other factors that influence the radicalisation process. By drawing on social identity theory, this paper offers a psycho-social explanation for how people define themselves in relation to their social group, as well as how the intra-group relationships can lead to extreme behaviour and resistance to counter efforts. These groups promote a salient social identity that becomes intrinsic to the self to the extent that members would risk their wellbeing, or that of others, to enhance or maintain their group’s cause